Practical Business Statistics - Croxton, Frederick Emory; Cowden, Dudley J. (Englewood Cliffs, N.J.: Prentice-Hall, 1960)
This book differs from the second edition and from many other books, in various respects: 1) statistical inference is introduced almost at the beginning of the book, at a very simple level; 2) in the early part of the book the range is used in making statistical inferences, rather than the more complicated standard error of the mean; 3) conventional methods of statistical inference occupy the bulk of the pages devoted to that topic, but there is a brief introduction to non-parametric methods; 4) the power of a test, and the operating characteristic of a test, are explained; 5) short and simple chapters are interspersed, as needed, on arithmetic, rounding of numbers, algebra, probability, and equations and curves; 6) orthogonal polynomials are introduced, and a short table of orthogonal polynomials is given in an appendix; 7) there is a unified treatment of growth curves; and 8) the idea of a mathematical model, and its relation to the method of analysis, is extensively treated in Chapter 39.
Includes index: p. 619-701.
ne 27/03/2018
Loans
Keywords: Statistics